Tehnološki vidik izvedbe možnega poseka in povezave z gozdnogospodarskim načrtovanjem - Košir, Boštjan (Gozdarski vestnik, 2008)
The article deals with connections between forest management planning and technological viewpoint of forest management. Presented is the influence of work concentration, composed of temporal, quality-economical and quantity viewpoint. More stress is laid to the quantity viewpoint consisting of tree size influence, cut intensity and work site size and concentration. The connections between individual factor and time or cost consumption are demonstrated on concrete examples. Individual cases which have not been published yet are treated in these results. The results of deliberations and analyses show that the forest management planning plays a very important role also for the operative work execution and the connected costs. Here, it is difficult to separate the influence of the long-term and executive forest management planning, since they are strongly connected. The work concentrationis not the only important factor affecting work economy and thereby also the forest owners' rents and their readiness and ability for investing in forests, but it is indisputably one of the most important factors. Key words: harvesting, technology, concentration, long term planning
Keywords: gozdnogospodarski načrti; technology; tehnologija; načrtovanje